Juvenile Justice Administrator Perspectives: Reframing Reentry Around Positive Youth Outcomes. (May 2021) - Dempsey, Michael P.; Davis, Wendi M.; Forbes, Peter; Penkoff, Cathleen Barclay; Gonsoulin, Simon; Harris, Phil W.
This article draws on research, policy, legislation, and practice to provide strategies for addressing the reentry needs of youth in the juvenile justice system and reframing the way successful reentry outcomes are conceptualized. Achieving a systemic paradigm shift of this nature requires that researchers, policymakers, and juvenile justice administrators work together to facilitate change. The Council of Juvenile Justice Administrators is leading the combined effort to facilitate reform in this area. This article briefly discusses the state of the juvenile justice system, progress in the field, and remaining challenges facing administrators of juvenile justice facilities, within the context of a changing framework that focuses on a developmental approach to issues of delinquency and emphasizes positive youth outcomes as a more effective measure of reentry.